2005
DOI: 10.1093/annonc/mdi003
|View full text |Cite|
|
Sign up to set email alerts
|

Cologne high-dose sequential chemotherapy in relapsed and refractory Hodgkin lymphoma: results of a large multicenter study of the German Hodgkin Lymphoma Study Group (GHSG)

Abstract: Based on the promising results of this study, a prospective randomized European intergroup study was started comparing this intensified regimen with two courses of DHAP followed by BEAM (HD-R2 protocol).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
2
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(70 citation statements)
references
References 27 publications
2
61
2
5
Order By: Relevance
“…These results compared favorably with the CR rate obtained after a single HCDT [18] and are similar to the overall response rate reported by the German Hodgkin Lymphoma Study Group on a recent large cohort of patients treated with high-dose sequential chemotherapy [21]. The FFP and OS rates for all patients are satisfactory.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results compared favorably with the CR rate obtained after a single HCDT [18] and are similar to the overall response rate reported by the German Hodgkin Lymphoma Study Group on a recent large cohort of patients treated with high-dose sequential chemotherapy [21]. The FFP and OS rates for all patients are satisfactory.…”
Section: Discussionsupporting
confidence: 86%
“…These include sequential HDCT [20,21] or more courses of HDCT [22], as reported for multiple myeloma [23]. Indeed, even in patients in complete remission after a single HDCT course, the assumption can be made that lymphoma cells are not detectable but still present, and are responsible for a subsequent relapse.…”
Section: Introductionmentioning
confidence: 99%
“…5,8 Like others, 3,[15][16][17] we have shown that patients with chemotherapy-sensitive disease have an improved PFS compared to patients who have SD. B symptoms at relapse have been shown to be associated with PFS in several studies, 3,18,19 however we and others 20,21 did not find a strong association between B symptoms at relapse and PFS. We also did not find any association between time to relapse or refractory disease and PFS, and the significance of these factors has also been variably reported in the literature.…”
Section: Discussioncontrasting
confidence: 71%
“…We also did not find any association between time to relapse or refractory disease and PFS, and the significance of these factors has also been variably reported in the literature. 2,[18][19][20][21][22] Immune reconstitution post-AHCT is a complex process whereby cells of the immune system recover at different rates, both in number, function and antigenetic spectrum that may influence tumor surveillance. 23 Our study that noted an association between pre-apheresis ALC and PFS does provide some support that overall immune recovery may be important in survival and that the ALC may represent a crude marker for immune reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…After IGEV chemotherapy, the patient refused an autologous stem cell transplantation. A PET Scan showed a complete remission, followed by yet another relapse one year later (Figure 3), treated with 3 cycles of dexamethasone, high dose cytarabine and cisplatin (DHAP) [9]. The 3 cycles of DHAP were followed by an autologous stem cell transplantation, with BEAM conditioning chemotherapy (high-dose carmustine, etoposide, cytarabine and melphalan), as described by the same German Hodgkin Lymphoma Study Group [10].…”
Section: Diagnosis and Previous Treatmentmentioning
confidence: 99%